(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the defining of non-verbal constituents of the opposition straight / crooked and the attempt to demonstrate their verbal realization in the English and Ukrainian languages is made. The close relationship of spatial concepts embodied in the framework of the opposition straight/crooked with cultural concepts and universal constants is shown.